Are there long-run implications of analyst coverage for IPOs? - Bradley, Daniel; Chan, Konan; Kim, Joonghyuk; Singh, Ajai (Journal of Banking & Finance, 2008)
Analyst coverage has been cited increasingly as an important attribute in the selection of an underwriter for a firm about to go public. However, it has also been alleged that affiliated analysts provide biased research. In this study, we examine these interrelated issues by examining the long-run performance of IPOs with coverage from their managing underwriters in a 1993–2003 sample. We find that (1) analysts’ research coverage from their managing syndicate is not related to long-run performance; (2) long-run performance is not different for firms that receive all-star analyst coverage; and (3) investors are not systematically worse off for following lead underwriter recommendations.